2007
DOI: 10.1016/j.solmat.2006.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal ageing on the stability of polymer bulk heterojunction solar cells

Abstract: A new approach is presented in order to improve the thermal stability of polymer:PCBM bulk heterojunction solar cells. The central idea in this approach is the use of a polymer with high glass transition temperature (T g ), well above the normal operating temperatures of the devices. In this paper a PPV-derivative with a T g of 150°C was used as electron donor and the thermal stability of the obtained solar cells was compared with solar cells based on the reference material Poly[2methoxy-5-(3',7'-dimethyloctyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 20 publications
5
105
0
3
Order By: Relevance
“…[45][46][47][48] However, applying this technique to polymer blends turned out less successful, again due to lack of contrast between the polymer phases. 49 An exception was presented by Blache et al, who applied environmental scanning EM (E-SEM) to PFB:F8BT blends and obtained well-resolved images.…”
Section: Toolbox To Probe the Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47][48] However, applying this technique to polymer blends turned out less successful, again due to lack of contrast between the polymer phases. 49 An exception was presented by Blache et al, who applied environmental scanning EM (E-SEM) to PFB:F8BT blends and obtained well-resolved images.…”
Section: Toolbox To Probe the Morphologymentioning
confidence: 99%
“…[45][46][47][48]54 These studies have been important for developing and understanding the device physics of polymer:fullerene PV devices. Similar studies on polymer blend PV devices are unfortunately still scarce.…”
Section: Factors Influencing the Morphology Of The Photoactive Layer mentioning
confidence: 99%
“…The behavior of BHJ OPVs with thermal degradation is generally correlated to morphological changes occurring in the active layer that can affect: i) charge separation process by formation of fullerene aggregates in polymer:fullerene blends, which leads to a PCE loss due to the reduction of the donor:acceptor (D:A) interfacial area [30][31][32], ii) charge extraction by a migration of a skinlayer of either polymer [33] or fullerene [34] adhering to the top contact, generating barriers or selective transport regions as a function of the device architecture; iii) transport properties by modification of the polymer packing in the blend [35,36], iv) recombination by an increase of the number of defect states at the bulk of the active layer [37], v) optical properties by generation of a charge transfer complex between donor and acceptor molecules which also acts as an exciton quencher [38]. Several works [31,32] demonstrated that morphological reorganization processes occur only if the solar cell is subjected to temperatures near or above the glass transition temperature (Tg) of the donor polymer. At this temperature devitrification of the blend allows the polymer and the fullerene molecules to rearrange/diffuse in the bulk and at the interface with the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, materials with high glass-transition temperatures have been used, resulting in a signifi cant improvement of the thermal stability of the photovoltaic parameters. [ 16 ] Transmission electron microscopy (TEM) studies have revealed that such improved thermal stability coincides with a more stable active layer morphology. The improvements are attributed to the reduced diffusion movement of the electron acceptor PCBM molecules within the active layer.…”
Section: Introductionmentioning
confidence: 99%